Evaluation of right ventricular longitudinal strain in pediatric patients with pulmonary hypertension by two-dimensional speckle-tracking echocardiography - Liu, Qianjun; Hu, Yuan; Chen, Wenjuan; Yao, Taoyue; Li, Wenfeng; Xiao, Zhenghui; Liu, Jinqiao; Xiao, Yunbin (Frontiers in Pediatrics, 2023)
Objectives We aimed to investigate the association between right ventricular longitudinal strain measured by two-dimensional speckle-tracking echocardiography (2D-STE) and right heart catheterization data in pediatric patients with pulmonary hypertension (PH). Methods Two groups were evaluated, each consisting of 58 patients. Group 1, patients with PH; Group 2, normal matched controls. Data were collected from 58 patients with PH who underwent invasive hemodynamic evaluation. Standard transthoracic echocardiographic assessment was performed in all patients under the same circumstances. All patients underwent 2D-STE, and off-line analysis generated right ventricle longitudinal strain (RVLS) and right ventricular free wall strain (RVFW) and collected echocardiographic conventional parameters of right ventricular function, including the control group. The relationship between invasive characteristics and right ventricular function parameters was analyzed. Results In all, 58 PH patients were included in our study. The mean pulmonary artery pressure (mPAP) and pulmonary vascular resistance (PVR) were strongly correlated with right ventricular free wall strain (RVFW) and right ventricular longitudinal strain (RVLS), moderately correlated with the right ventricle myocardial performance index (Tei index), weakly correlated with the transverse diameter of the right ventricle(RV) and the transverse diameter of the right atrium (RA), and moderately negatively correlated with right ventricular fractional area change (RVFAC). In terms of segments of the right ventricular free wall, the basal segment had the highest correlation coefficient with mPAP and PVR (r=0.413, 0.523, 0.578, r=0.421, 0.533, 0.575, p<0.05, respectively). Tricuspid annular plane systolic excursion (TAPSE), main pulmonary artery diameter (MPA), peak systolic velocity of the right ventricle (RV-S’) and RA area parameters were not associated with mPAP and PVR (p>0.05). Conclusions Right ventricular longitudinal strain is a reliable indicator to evaluate right ventricular function in pediatric patients with PH. It can provide valuable reference information for the clinical judgment of the status and severity of the disease in children.